Implementasi Teknik Hand Held Fan Terhadap Penurunan Sesak Nafas pada Pasien dengan Congestive Heart Failure - Yusrina Ammazida (Sahabat Publikasi Kuu, 2023)
Background : CHF is a clinical syndrome that can cause structural/functional problems in the heart, thus interfering with the ability of the ventricles to receive/pump enough blood to meet the body's metabolic needs. A symptom often experienced by CHF patients is shortness of breath (dyspnea). Dyspnea that occurs in CHF patients can have an impact on their physical, psychological, and emotional health. Patients with dyspnea feel more comfortable in front of a fan. Purposes : This study to determine the effect of hand held fan therapy on reducing dyspnea in Congestive Heart Failure patients. Method : The method used in writing is a case report which is carried out for 3 days. Administration of hand held fan therapy is carried out in CHF patients with dyspnea. Results : The administration of hand held fan therapy in CHF patients there was a decrease in dyspnea although not significant, characterized by a dyspnea scale decreased from a scale of 5 to a scale of 2, breathing frequency from 26x / minute to 22x / minute, SPO2 : <96% to 99%. Conclusions : Combination therapy of pharmacological therapy is hand held fan therapy can reduce the condition of shortness of breath experienced in CHF patients. Although shortness of breath is still felt, but the therapy is able to reduce the appearance of shortness of breath again. Accuracy in applying the therapy accompanied by pharmacological therapy gets optimal results in reducing shortness of breath from before the intervention to after the intervention is carried out.